IJCM_318A: Risk Factors for Anaemia among Type 2 Diabetes Mellitus Patients in Mangalore- A Case Control Study. - Rekha T; Ramakrishnan Mahima Advaitha; Archa KR; Dahiya Navneet; Chopdar Ankita; Sharma Vagish; Unnikrishnan Bhaskaran; Mithra Prasanna; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: Anaemia, a common haematological abnormality, currently stands at a prevalence rate of 24.8% worldwide and 39.86% in India, affecting 1.62 billion individuals overall. Studies have shown that patients with Diabetes are twice as likely to be prone to anaemia. Objective: To study the risk factors for anaemia among patients with type 2 Diabetes Mellitus. Methodology: This is a record-based case-control study of 50 cases (diabetic with anaemia) and 100 controls (diabetic without anaemia) in Government Wenlock Hospital, Mangalore. Patients with haemoglobin concentration below the normal level (as defined by WHO as <13 g/dl for men and <12 g/dl for women) were considered anaemic. Data was entered and analyzed using the statistical software SPSS Version 17.0. Univariate analyses and a Chi-Square test were conducted to identify risk factors. Results: The median age of cases as well as controls was 60 years. The duration of diabetes was 8 years in cases and 7 years in controls. Among 50 cases, there were 39 (78%) males and 11(22%) females and among 100 controls, 68(68%) males and 32(32%) females. On univariate analysis, it was found that the low serum urea, creatinine, albumin, total protein and calcium levels were significantly associated with the presence of anaemia (P <0.05). Conclusion: The above parameters implicate impairment in renal function and hence we can conclude that impaired renal function is a risk factor for developing anaemia in type 2 Diabetes Mellitus patients.